(untitled) (Research, Society and Development, 2020)
Introduction: Nursing health training was centered on the rigid reiteration of tasks. However, in the face of contemporaneity, there is a need for changes in nursing education, with the adoption of alternative teaching methods, such as the use of active methodologies. Methodology: This article is an experience report that aimed to describe the experience of using the problematization methodology through the Arch of Charles de Maguerez in the teaching of the Educational Practices for Nursing discipline and to share repercussions on the learning process of the students. students when addressing the theme Active Methodology as the Problematization and Problem-Based Learning, using the Arch of Charles Maguerez, following the steps of observing reality, key points, theorizing, hypothesis of solution and application in reality. Results: The participation of students, the encouragement of reasoning, the application of the concepts to their reality allowed effective participation of students, constructive teacher-student exchanges and a dynamic and evolving teaching-learning process. Conclusion: This lived experience, based on the pedagogical proposal, was significant and allowed students / teachers to rethink and reconstruct their own pedagogical practices.